Analysis Of Market Power And Efficiency Of Islamic Banking: Evidence From Indonesia - Rakhi, Hayet (Indonesian Journal of Islamic Business and Economics (IJIBE), 2024)
Financial integration and economic openness drive Islamic banking to enhance competitiveness and efficiency. This research aims to analyze the development of market power and efficiency of Islamic banking in Indonesia. Market power is assessed using the Lerner Index and the Herfindahl-Hirschman Index, while technical efficiency and scale efficiency are evaluated using Data Envelopment Analysis (DEA). This study utilizes quarterly data from 2014 to 2020, focusing on 14 Islamic commercial banks as observation objects. The findings reveal that the market power (Lerner index) of Islamic banking at the interbank level falls into the category of moderate competition, whereas at the industry level (HHI), Islamic banking exhibits relatively high concentration, indicating intense oligopolistic competition. The technical efficiency achievement of Islamic banking is categorized as low, while scale efficiency achievement falls into the moderate category. This research encourages the government, through the Financial Services Authority (OJK), to monitor the market concentration level of Islamic banking to ensure healthy industry competition and enhance bank efficiency through policies and projections concerning potential mergers and spin-offs in Islamic banking.